2006
DOI: 10.1002/jctb.1442
|View full text |Cite
|
Sign up to set email alerts
|

Self‐aggregated nanoparticles composed of periodate‐oxidized dextran and cholic acid: preparation, stabilization and in‐vitro drug release

Abstract: A novel method was used to synthesize cholic acid hydrophobic-modified dextrans (CAH-Dex) which form nanoparticles in aqueous solution. The stabilization and drug-loading of the formed nanoparticles were investigated. Dextran was oxidized by sodium periodate to dextran dialdehyde which was then conjugated with cholic acid hydrazide through an acyl hydrazone linkage. The self-aggregation behavior of the resulting conjugates was investigated using nuclear magnetic resonance, fluorescence and photo correlation sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…The thickness of the cholate unit is about 0.5 nm [20c] and the distance between p-stackings of PPE is estimated as about 0.4 nm. [22] It has been generally recognized that bile acid derivatives tend to assemble in a headto-tail fashion with two distinguishable faces of the cholates tilted up and down alternately, [20] whereas PPE derivatives with long alkyl or alkoxy groups were expected to form a lamellar or doubly lamellar morphology in which the structure of the polymer is dominated by side-chain packing. [23] Based on the data and results described above, we proposed that the molecular packing in the membrane of the formed vesicular structure has a multilayer lamellar structure through a combination of hydrogen bonding, hydrophobic interaction, and p-p stacking, in which the conjugated molecule is arranged in a highly organized pattern and the bile acid units are in an antiparallel interlocked configuration (Figure 8b).…”
Section: Mechanism Of Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the cholate unit is about 0.5 nm [20c] and the distance between p-stackings of PPE is estimated as about 0.4 nm. [22] It has been generally recognized that bile acid derivatives tend to assemble in a headto-tail fashion with two distinguishable faces of the cholates tilted up and down alternately, [20] whereas PPE derivatives with long alkyl or alkoxy groups were expected to form a lamellar or doubly lamellar morphology in which the structure of the polymer is dominated by side-chain packing. [23] Based on the data and results described above, we proposed that the molecular packing in the membrane of the formed vesicular structure has a multilayer lamellar structure through a combination of hydrogen bonding, hydrophobic interaction, and p-p stacking, in which the conjugated molecule is arranged in a highly organized pattern and the bile acid units are in an antiparallel interlocked configuration (Figure 8b).…”
Section: Mechanism Of Self-assemblymentioning
confidence: 99%
“…[20] The mechanism of their formation is quite complex and often involves complicated "secondary assemblies". Figure 8a summarizes the aggregation behavior of cholic acid decorated PPE, which shows different buildups of supramolecular assemblies dependent upon the conditions used.…”
Section: Mechanism Of Self-assemblymentioning
confidence: 99%
“…Very recently there are two reports of antimicrobial activity of cholic acid derivatives [3,4,18,19]. Willemen et al reported that the antimicrobial activity of cholic acid against Escherichia coli and Enterobacter faecalis could be enhanced through introducing the cationic trimethylammonium groups [20].…”
Section: Introductionmentioning
confidence: 97%
“…Polymers can be modified to introduce -CHO groups, followed by derivation with bile acids (Figure 10) [59][60] .…”
Section: Bile Acids As Pendent Groups Of Polymersmentioning
confidence: 99%
“…Bile acids are often attached as pendent groups to polysaccharides (chitosan [50][51][52] , glycol chitosan [53][54][55][56] , heparin [57] , dextran [58][59][60] or cellulose [61] ) or proteins (bovine serum albumin) [62,63] via ester or amide bonds (Figure 9) [64] . Polymers can be modified to introduce -CHO groups, followed by derivation with bile acids (Figure 10) [59][60] .…”
Section: Bile Acids As Pendent Groups Of Polymersmentioning
confidence: 99%